2011
DOI: 10.1111/j.1365-2966.2011.18932.x
|View full text |Cite
|
Sign up to set email alerts
|

Galactic ménage à trois: simulating magnetic fields in colliding galaxies

Abstract: We present high‐resolution simulations of a multiple merger of three disc galaxies, including the evolution of magnetic fields, performed with the N‐body/smoothed particle hydrodynamics (SPH) code Gadget. For the first time, we embed the galaxies in a magnetized, low‐density medium, thus modelling an ambient intergalactic medium (IGM). The simulations include radiative cooling and a model for star formation and supernova feedback. Magnetohydrodynamics is followed using the SPH method. The progenitor discs have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
65
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 76 publications
(130 reference statements)
12
65
3
Order By: Relevance
“…We have performed simulations of three colliding galaxies to proof the saturation and equipartition phenomena seen in Kotarba et al, 2010a on the basis of a more general setup (Kotarba et al, 2010b). In these simulations, the magnetic field saturates at a value of about 1 G -which is again consistent with observations -, independent of the initial value.…”
Section: Simulationssupporting
confidence: 49%
“…We have performed simulations of three colliding galaxies to proof the saturation and equipartition phenomena seen in Kotarba et al, 2010a on the basis of a more general setup (Kotarba et al, 2010b). In these simulations, the magnetic field saturates at a value of about 1 G -which is again consistent with observations -, independent of the initial value.…”
Section: Simulationssupporting
confidence: 49%
“…The above turbulent dynamo scenario can be sustaining the magnetic fields in the ICM (Brandenburg & Subramanian 2005;Brandenburg et al 2012;de Gouveia Dal Pino et al 2013, and references therein). This picture is supported by MHD simulations of galaxy mergers, showing the amplification of the magnetic field in the intergalactic medium (Kotarba et al 2011).…”
Section: Introductionmentioning
confidence: 63%
“…This would have a significant influence on the proton-to-electron ratio in the intergalactic medium and significantly influence theoretical predictions of the propagation of cosmic rays and the strength of magnetic fields in the intergalactic space. In simulations of three interacting galaxies Kotarba et al (2011) showed, that the whole group medium can become magnetised over a timescale of several hundred Myr.…”
Section: Discussionmentioning
confidence: 99%